Co3[Fe(CN)6]2 nanocube derived architecture of Co, Fe co-doped MoS2 nanosheets for efficient water electrolysis. (20th June 2019) - Si, Chongdian; Wu, Yanhua; Sun, Yanfang; Liu, Qingyun; Tang, Lin; Zhang, Xiao; Guo, Jinxue
Abstract: Developing nonprecious and high-efficiency bifunctional electrocatalyst towards overall water splitting is of fundamental importance for future renewable fuel system and is still a big challenge. MoS2 is regarded as a promising candidate, but effective techniques are lacking to simultaneously settle the obstacles of limited site density and intrinsic activity, which still restrict its practical application. Herein, we address such challenges via activating MoS2 with Co, Fe co-doping and nanostructure engineering techniques through a template confined strategy. Using Prussian blue analogue (PBA) of Co3 [Fe(CN)6 ]2 nanocubes as self-sacrifice template not only guides the specific geometry of Co, Fe co-doped MoS2 (Co, Fe-MoS2 ) nanosheets assembled architecture, but also achieves the Co, Fe co-doping. Nanosheets assembled architecture supplies structural benefits of high surface area, short charge transfer path, and easily accessible active sites. The Co, Fe co-doping induces defects as additional catalytic sites and alters the electronic structure of active sites. When used as bifunctional catalysts for water electrolysis, Co, Fe-MoS2 shows excellent catalytic activity with a low cell potential of 1.49 V at a current density of 10 mA cm −2 . In a two-electrode electrolyzer, only one single-cell AA battery could afford the sustainable overall water splitting. Highlights: Co, Fe co-doped MoS2 nanosheets assembled architecture is prepared. Synergism of doping and structure advantages is beneficial for catalysis. Excellent HER and OER performances are obtained in KOH. Co, Fe-MoS2 serves as bifunctional catalyst for overall water splitting.